Community phylogenetic analysis of moderately thermophilic cyanobacterial mats from China, the Philippines and Thailand - Hongmei J. (2014)
Most community molecular studies of thermophilic cyanobacterial mats to date have focused on Synechococcus occurring at temperatures of ∼50-65°C. These reveal that molecular diversity exceeds that indicated by morphology, and that phylogeographic lineages exist. The moderately thermophilic and generally filamentous cyanobacterial mat communities occurring at lower temperatures have not previously been investigated at the community molecular level. Here we report community diversity in mats of 42-53°C recovered from previously unstudied geothermal locations. Separation of 16S rRNA gene-defined genotypes from community DNA was achieved by DGGE. Genotypic diversity was greater than morphotype diversity in all mats sampled, although genotypes generally corresponded to observed morphotypes. Thirty-six sequences were recovered from DGGE bands. Phylogenetic analyses revealed these to form novel thermophilic lineages distinct from their mesophilic counterparts, within Calothrix, Cyanothece, Fischerella, Phormidium, Pleurocapsa, Oscillatoria and Synechococcus. Where filamentous cyanobacterial sequences belonging to the same genus were recovered from the same site, these were generally closely affiliated. Location-specific sequences were observed for some genotypes recovered from geochemically similar yet spatially separated sites, thus providing evidence for phylogeographic lineages that evolve in isolation. Other genotypes were more closely affiliated to geographically remote counterparts from similar habitats suggesting that adaptation to certain niches is also important. © Springer-Verlag 2005.